Sie sind auf Seite 1von 10

Numerical Analysis Practice Exam Question 2014 - 2015

dy
1. a) Apply Euler’s method to solve the equation = 2x  y
dx
Find y1 , y2 and y3 given that x0 = 0, y0 = 1 and h = 0.2
dy
b) Apply the modified Euler method to solve the equation = x 3 − xy
dx
Find y1 , y2 and y3 given that x0 = 1, y0 = 1 and h = 0.1

dy
2. a) Apply Euler’s method to solve the equation = 3x  y
dx
Find y1 y2 y3 , y4 and y5 given that x0 = 0, y0 = 1 and h = 0.2
dy xy
b) Apply the modified Euler method to solve the equation =
dx xy
Find y1 y2 and y3 given that x0 = 1.0, y0 = 1.0 and h = 0.1

3.a) Use tables to find the z transforms of the following


i) 2k ii) (4) k iii) 3  (5) k
b) Solve the following second order difference equation using z transforms
yk + 2  2yk + 1 + yk = 0 given that y0 = 1 and y1 = 3

4.a) Use tables to find the inverse z transforms of the following


z 2z
i) ii)
z3 z5
z 6z
iii) iv)
2z  1 (z  3) 2
b) Solve the following first order difference equation using z transforms
2y k + 1  yk = 2 k given that y0 = 3

5.a) Use tables to find the z transforms of the following


i) 3k ii) (5) k iii) 2  (4) k
b) Solve the following second order difference equation using z transforms
yk + 2 + 3yk + 1 + 2yk = 0 given that y0 = 0 and y1 = 1

6.a) Use tables to find the inverse z transforms of the following


z 2z z 8z
i) ii) iii) iv)
z2 z7 3z  1 (z  4) 2
b) Solve the following first order difference equations using z transforms
2yk + 1  yk = 2k given that y0 = 1

7. Find the eigenvalues and eigenvectors for matrix A

 2 7 0
A=
1 3 1 
 
5 0 8

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 1
Numerical Analysis Practice Exam Question 2014 - 2015

8.a) Solve the following simultaneous equations eigenvalues and eigenvectors

x1  x 1  2x 2
x 2  3x 1  4 x 2

1 2 0 
Using A  MS M find A if A  
n n 3
b) 
6  1

9. Determine the Fourier series for the following;

a) f(x)

4
x
 2 3 4 5 6 7

b) f(x)

x
/2 /2 3/2 5/2 7/2 9/2
c) f(x)
3

3  2 3 4 5 6 7 x

d) f(x)
3
  2 3 4 5 6 7
x
3

e) f(x)

x
 2 3 4 5 6 7

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 2
Numerical Analysis Practice Exam Question 2014 - 2015

Feedback (worked solutions)

1.a) Using xr + 1 = xr + h and yr + 1 = yr + h[f(xr , yr )]


x0 = 0 , y0 = 1 and h = 0.2
y1 = y0 +0.2[f(x0, y0 )]
y1 = 1 + 0.2[f(0 , 1)]
y1 = 1 + 0.2[2×0  1]
y1 = 1 + 0.2[−1]
y1 = 0.8
and x1 = 0.2

y2 = y1 +0.2[f(x1, y1 )]
y2 = 0.8 + 0.2[f(0.2 , 0.8)]
y2 = 0.8 + 0.2[2×0.2 0.8]
y2 = 0.8 + 0.2[−0.4]
y2 = 0.72
and x2 = 0.4

y3 = y2 +0.2[f(x2, y2 )]
y3 = 0.72 + 0.2[f(0.4 , 0.72)]
y3 = 0.72 + 0.2[2×0.4  0.72]
y3 = 0.72 + 0.2[0.08]
y3 = 0.736
and x3 = 0.6

dy
1.b) = x 3 − xy for x = 1.0(0.1)1.3 given that y = 1 when x = 1 and h = 0.1
dx

y *r + 1 = yr + h[f(xr , yr )]
h
yr + 1 = yr + [f(xr , yr ) + f(xr + 1 , y*r + 1)] and x r 1  x r  h
2
x0 = 1, y0 = 1

x1 = 1 + 0.1 = 1.1

y*1 = yo + h× f(x0, y0) = 1 + 0.1 × f(1,1) = 1 + 0.1 × (1 3 – 1x1) = 1

h 0 .1
y1 = y0 + [f(x0 , y0 ) + f(x1 , y*1)] = 1 + [f(1,1) + f(1.1,1.0)]
2 2
0 .1 3
=1+ [(1 – 1x1) + (1.1 3 – 1.1x1)]
2
0 .1 0 .1
= 1+ [0 + 0.231] = 1 + [0.11] = 1.01155
2 2

x2 = 1.1 + 0.1 = 1.2


y*2 = y1 + h× f(x1, y1) = 1.01155 + 0.1 × f(1.1, 1.01155) =

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 3
Numerical Analysis Practice Exam Question 2014 - 2015

= 1.01155 + 0.1 × (1.1 3 – 1.1x1.01155) = 1.0333795

h
y2 = y1 + [f(x1 , y1 ) + f(x2 , y*2)]
2
0 .1
= 1.01155 + [f(1.1,1.01155) + f(1.2,1.0333795)]
2
0 .1
= 1.01155 + [(1.1 3 – 1.1x1.01155) + (1.2 3 – 1.2x1.0333795)]
2
0 .1
= 1.01155 + [0.218295 + 0.4879446]
2
0 .1
= 1.01155 + [0.7062396] = 1.04686198
2
x3 = 1.2 + 0.1 = 1.3
y*3 = y2 + h× f(x2, y2) = 1.04686198+ 0.1 × f(1.2, 1.04686198) =
= 1.04686198+ 0.1 × (1.2 3 – 1.2x1.04686198) = 1.094038542
h
Y3 = y2 + [f(x2 , y2 ) + f(x3 , y*3)]
2
0 .1
= 1.04686198 + [f(1.2, 1.04686198) + f(1.3,1.094038542)]
2
0 .1
= 1.04686198 + [(1.2 3 – 1.2x1.04686198) + (1.3 3 – 1.3x1.094038542)]
2
0 .1
= 1.04686198 + [0.471765624 + 0.774749895]
2
0 .1
= 1.04686198 + [1.246515519] = 1.109187756
2

2.a) Using xr + 1 = xr + h and yr + 1 = yr + h[f(xr , yr )]


x0 = 0 , y0 = 1 and h = 0.2
x1 = 0.2
y1 = y0 +0.2[f(x0, y0 )]
y1 = 1 + 0.2[f(0 , 1)]
y1 = 1 + 0.2[1]
y1 = 0.8

x2 = 0.4
y2 = y1 + 0.2[f(x1 , y1 )]
y2 = 0.8 + 0.2[f(0.2 , 0.8)]
y2 = 0.8 + 0.2[30.2  0.8)]
y2 = 0.8 + 0.2[0.2]
y2 = 0.76

x3 = 0.6
y3 = y2 + 0.2[f(x2 , y2 )]
y3 = 0.76 + 0.2[f(0.4 , 0.76)]

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 4
Numerical Analysis Practice Exam Question 2014 - 2015

y3 = 0.76 + 0.2[f(3  0.4  0.76)]


y3 = 0.76 + 0.2[0.44]
y3 = 0.848

x4 = 0.8
y4 = y3 + 0.2[f(x3 , y3 )]
y4 = 0.848 + 0.2[f(0.6 , 0.848)]
y4 = 0.848 + 0.2[f(3  0.6  0.848)]
y4 = 0.848 + 0.2[0.952]
y4 = 1.0384

x5 = 1.0
y5 = y4 + 0.2[f(x4 , y4 )]
y5 = 1.0384 + 0.2[f(0.8 , 1.0384)]
y5 = 1.0384 + 0.2[f(3  0.8  1.0384)]
y5 = 1.0384 + 0.2[1.3616]
y5 = 1.31072

2.b)
11
y1* = y0 + hf(x0,y0) = 1 + 0.1  f(1,1) = 1 + 0.1  ( ) = 1.2
1 1
 f(x 0 , y 0 )  f(x 1 , y1* )   f(1,1)  f(1.1,1.2) 
y1 = y0 + h    = 1 + 0.1   
 2   2 
 11 1.1  1.2 
(
 1  1 )  ( )
1. 1  1. 2   2  1.742424 
= 1 + 0.1    = 1 + 0.1    = 1.1871212
 2   2 
 
x2 = 1.2, y2* = 1.362268,
y2 = 1.353065

x3 = 1.3, y3* = 1.510304,


y3 = 1.50322

z
3.a) i) Z{2 k } =
z2
z
ii) Z{(4) k} =
z4
3z
iii) Z{3  (5) k} =
z5
3.b) yk + 2  2yk + 1 + yk = 0, given that y0 = 1 and y1 = 3
[z 2 y(z)  z 2 y0  zy1]  2[zy(z)  zy0] + y(z) = 0
[z 2 y(z)  z 2(1)  z(3)]  2[zy(z)  z(1)] + y(z) = 0
z 2 y(z)  z 2  3z  2zy(z) + 2z + y(z) = 0
z 2 y(z)  2zy(z) + y(z) = z 2 + z

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 5
Numerical Analysis Practice Exam Question 2014 - 2015

y(z)[z 2  2z + 1] = z 2 + z
y(z)[z 2  2z + 1] = z 2 + z
y(z)(z  1)(z  1) = z 2 + z
z2  z Az Bz
y(z) = = 
(z  1) 2 (z  1) 2
(z  1)
z2  z Az  Bz(z  1)
= =
(z  1) 2 (z  1) 2
Let z = 1
12 + 1 = A(1)  2=A
Let z = 2
22 + 2 = A(2) + B(2)(2  1)
4 + 2 = 2A + 2B  B=1
2z z
y(z) = 
(z  1) 2
(z  1)
yk = 2k + 1

z
4.a) i) Z  1{ } = 3k
z3
2z
ii) Z  1{ } = 2  (5) k
z5
z z 1 1
iii) Z  1{ } = Z  1{ } = ( ) k
2z  1 2(z  1 ) 2 2
2
6z 3z
iv) Z  1{ } = Z  1{ 2 } = 2k(3) k
(z  3) 2
(z  3) 2

4.b) 2yk + 1  y k = 2 k y0 = 3
z
2[zy(z)  zy0] y(z) =
z2
z
2zy(z)  6z  y(z) =
z2
z 6z 2  11z
y(z)[2z  1] = + 6z =
z2 (z  2)
6z 2  11z Az Bz Az(z  2)  Bz(2z  1)
y(z) = =  =
(2z  1)(z  2) 2z  1 z  2 (2z  1)(z  2)
1
Let z = 2 24  22 = B(2)(4  1)  2 = 6B  B=
3
1 16
Let z = 1.5  5.5 = A(0.5)(0.5  2)  4 = 0.75A  A=
2 3

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 6
Numerical Analysis Practice Exam Question 2014 - 2015

16 1 16 1
z z z z
y(z) = 3  3  3  3
2z  1 z  2 2(z  12 ) z  2
8 1 k 1
 yk = ( ) + (2) k
3 2 3
z
5.a) i) Z{3 k } =
z3
z
ii) Z{(5) k} =
z5
2z
iii) Z{2  (4) k} =
z4
5.b) yk + 2 + 3yk + 1 + 2yk = 0 (y0 = 0 and y1 = 1)
(z2 Y(z)  z2 y0 zy1 ) + 3(zY(z)  zy0 ) + 2Y(z) = 0
z2Y(z)  z + 3zY(z) + 2Y(z) = 0
Y(z)[z2 + 3z + 2]  z = 0
Y(z)(z + 1)(z + 2) = z
z Az Bz
Y(z) = = 
(z  1)(z  2) (z  1) (z  2)
z Az(z  2) + Bz(z  1)
Y(z) = =
(z  1)(z  2) (z  1)(z  2)
Y(z) = z = Az(z + 2) + Bz(z + 1)
Let z = 1 1 = A(1)(1 + 2)  A=1
Let z = 2 2 = B(2)(2 + 1)
2 = 2B  B = 1
z z
Y(z) = 
(z  1) (z  2)
yk = (1) k  (2) k

z
6.a) i) Z  1{ } = 2k
z2
2z
ii) Z  1{ } = 2  (7) k
z7
z z 1 1
iii) Z  1{ } = Z  1{ } = ( ) k
3z  1 3(z  1 ) 3 3
3
8z 4z
iv) Z  1{ } = Z  1{ 2 } = 2k(4) k
(z  4) 2
(z  4) 2

6.b) 2yk + 1  yk = 2 k (y0 = 1)


z
2[zy(z)  zy0]  y(z) =
z2
z
2zy(z)  2z  y(z) =
z2

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 7
Numerical Analysis Practice Exam Question 2014 - 2015

z 2z 2  3z
y(z)[2z  1] = + 2z =
z2 (z  2)
2z 2  3z
y(z) =
(2z  1)(z  2)
2z 2  3z Az Bz Az(z  2)  Bz(2z  1)
  
(2z  1)(z  2) (2z  1) (z  2) (2z  1)(z  2)
Let z = 2 22 2  32 = B(2)(4  1)
8  6 = 6B
1
2 = 6B  B=
3
Let z = 1 2( 1 ) 2  3  1 = A( 1 )( 1  2)
2 2 2 2 2
1  3=3A A=
4
2 2 4 3
4 z 1 z k
3 3 21 1
y(z) =  so yk =   + (2)k
2z  1 z  2 3 2 3

9.a)
1 π 1 1
a0 = ∫ 4 dx = [4x]π0 = π [4π − 0] = 4
π 0 π
an = 0 for all n
1 π 1 4 π 4
bn = π ∫0 4sin(nx) dx = [
π n
cos(nx)] = nπ [cos(nπ) − cos(0)]
0
4
= [cos(nπ) − 1]

now cos(nπ) = 1 when n is even and cos (nπ) = −1 when n is odd
So bn = 0 when n is even
8
bn = − when n is odd

8 1 1 1 1
f(x) = 2 – nπ [sin(𝑥) + 3 sin(3𝑥) + 5 sin(5𝑥) + 7 sin(7𝑥) + 9 sin(9𝑥) + . . .

9.b)
a0 = 3
1 π⁄ 1 3 π 3 nπ nπ
an = π ∫−π⁄2 3cos(nx) dx = [
π n
sin(nx)] = nπ [sin( 2 ) − sin(− 2
)]
2 0
3 nπ nπ 3 nπ 6 nπ
= nπ
[sin ( 2 ) + sin( 2 )] = nπ
[2sin( 2 )] = nπ [sin( 2 )]
an = 0 when n is even

6
= nπ when n is 1,5,9,13

−6
= nπ when n is 3,7,11,15

6 1 1 1 1
f(x) = 1.5 + π [cos(x) − 3 cos(3x) + 5 cos(5x) − 7 cos(7x) + 9 cos(9x) − . .

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 8
Numerical Analysis Practice Exam Question 2014 - 2015

 2 7 0
7. A=
1 3 1 
 
5 0 8

2  λ 7 0 
 1 3 λ 1 3λ
1 
1 1 1
3λ so (2  λ) 7 0 =0
 0 8λ 5 8λ 5 0
 5 0 8  λ 

(2 ─ λ)[(3 ─ λ)(8 ─ λ) ─ 0] ─ 7[(1(8 ─ λ) ─ 5] + 0[0 ─ 5(3 ─ λ)] = 0

(2 ─ λ)[(3 ─ λ)(8 ─ λ)] ─ 7[(8 ─ λ) ─ 5] = 0

(2 ─ λ)[(3 ─ λ)(8 ─ λ)] ─ 7(3 ─ λ) = 0

(3 ─ λ)[(2 ─ λ)(8 ─ λ) ─ 7] = 0

(3 ─ λ)[(16 ─ 8λ ─ 2λ + λ 2 ─ 7] = 0

(3 ─ λ)(λ 2 ─ 10λ + 9) = 0

(3 ─ λ)(λ ─ 1)(λ ─ 9) = 0

λ = 1, 3 and 9

λ=1

x1 + 7x2 =0

x1 + 2x2 + x3 = 0

5x1 + 7x3 = 0

7
  1
 
 5

λ=3

─x1 + 7x2 =0

x1 =0

5x1 + 5x3 = 0

7 
1 
 
  7 

λ=9

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 9
Numerical Analysis Practice Exam Question 2014 - 2015

─7x1 + 7x2 =0

x1 ─ 6x2 + x3 = 0

5x1 ─ x3 = 0

1
1
 
5

1 λ 2
8.a) =0
3 4λ

(1  )(4  )  6 = 0

4   + 4 + 2  6 = 0

2 + 3  10 = 0

(  2)( + 5) = 0   = 2 or 5

=2  = 5

x1 + 2x2 = 0 6x1 + 2x2 = 0

2 1
3x1  6x2 = 0 1  3x1 + x2 = 0  
   3

 2 1
x =   (C1e 2t
 D1 e  2t
)    (C 2 Cos 5t  D 2Sin 5t)
1  3

1 0  2 0  1
 1 0
8.b) M=   ,S= 0 1 , M =  2 1
2 1    
3
3 3 1
1 0   2 0   1 0 
A =MS M =     
2 1 0  1  2 1

1 0   2 3 0   1 0
=    
2 1  0 (1) 3   2 1

1 0  8 0   1 0 
=    1 marks
2 1 0 1  2 1

 8 0   1 0 8 0 
=    =  
16 1  2 1 18 1

Mjbs/NumericalAnalysis/NumericalAnalysisUG2PracticeExamquestion1415 10